Iron-containing micronutrient powders modify the effect of oral antibiotics on the infant gut microbiome and increase post-antibiotic diarrhoea risk: a controlled study in Kenya. Issue 4 (17th November 2018) - Paganini, Daniela; Uyoga, Mary A; Kortman, Guus A M; Cercamondi, Colin I; Winkler, Hans C; Boekhorst, Jos; Moretti, Diego; Lacroix, Christophe; Karanja, Simon; Zimmermann, Michael B
Abstract : Objective: Many African infants receiving iron fortificants also receive antibiotics. Antibiotic efficacy against enteropathogens may be modified by high colonic iron concentrations. In this study, we evaluated the effect of antibiotics on the infant gut microbiome and diarrhoea when given with or without iron-containing micronutrient powders (MNPs). Design: In a controlled intervention trial, four groups of community-dwelling infants (n=28; aged 8–10 months) received either: (A) antibiotics for 5 days and iron-MNPs for 40 days (Fe + Ab + ); (B) antibiotics and no-iron-MNPs (Fe − Ab + ); (C) no antibiotics and iron-MNPs (Fe + Ab − ); or (D) no antibiotics and no-iron-MNPs (Fe − Ab − ). We collected a faecal sample before the first antibiotic dose (D0) and after 5, 10, 20 and 40 days (D5–D40) to assess the gut microbiome composition by 16S profiling, enteropathogens by quantitative PCR, faecal calprotectin and pH and assessed morbidity over the 40-day study period. Results: In Fe + Ab +, there was a decrease in Bifidobacterium abundances (p<0.05), but no decrease in Fe − Ab + . In Fe − Ab +, there was a decrease in abundances of pathogenic Escherichia coli (p<0.05), but no decrease in Fe + Ab + . In Fe − Ab +, there was a decrease in pH (p<0.05), but no decrease in Fe + Ab + . Longitudinal prevalence of diarrhoea was higher in Fe + Ab + (19.6%) compared with Fe − Ab + (12.4%) (p=0.04) and compared with Fe + Ab − (5.2%) (p=0.00). Conclusion: Our findings need confirmation in a larger study but suggest that, in African infants, iron fortification modifies the response to broad-spectrum antibiotics: iron may reduce their efficacy against potential enteropathogens, particularly pathogenic E. coli, and may increase risk for diarrhoea. Trial registration number: NCT02118402 ; Pre-results.